2020
DOI: 10.23887/jpi-undiksha.v9i3.17736
|View full text |Cite
|
Sign up to set email alerts
|

The Demonstration of Linguistic, Cognitive and Socio-cultural Dimensions of Academic Literacy in Nursing Students’ Written Texts

Abstract: This study aimed to evaluate the demonstration of linguistic, cognitive, and socio-cultural dimensions of academic literacy in the written texts produced by the students of the nursing program. A descriptive qualitative research design was used to meet the purpose of the study. Data were collected from the students’ written texts, which served as the students’ responses to an English quiz. Fifteen out of fifty-two students’ written texts were randomly selected for the analysis. A modified scale table from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…This also involves written communication skills, as they must write in a standardized, clear, and precise manner within the documents. Writing skills can be honed through tasks such as composing description assignments, responding to questions, producing papers, drafting reports, delivering presentations, and answering queries (Dursun et al, 2020;Moore & Morton, 2017;Nurakhir et al, 2020). The assessment of group presentation communication skills is conducted descriptively within the student worksheet.…”
Section: The Effect Of Implementing Webinar Tutorials In Flipped Clas...mentioning
confidence: 99%
“…This also involves written communication skills, as they must write in a standardized, clear, and precise manner within the documents. Writing skills can be honed through tasks such as composing description assignments, responding to questions, producing papers, drafting reports, delivering presentations, and answering queries (Dursun et al, 2020;Moore & Morton, 2017;Nurakhir et al, 2020). The assessment of group presentation communication skills is conducted descriptively within the student worksheet.…”
Section: The Effect Of Implementing Webinar Tutorials In Flipped Clas...mentioning
confidence: 99%
“…Based on the literature review, there are several strategies suggested and has found to be effective in enhancing the students' communication skills such as questioning and answering (Mohd, 2020), independent discussions, task-based instructions, jigsaw puzzle, games, problem solving, drama, role-play, group activities, pairwork and oral reading (Khalil, 2019). Inter-class debate activity among students is also effective in enhancing the students's communication skills, (Nurakhir et al, 2020) in teaching a language.…”
Section: Literature Review Communicationmentioning
confidence: 99%